Teaching Probability Theory and Mathematical Statistics with Practical Problems - Yusubjanova Musharraf Tursunali Kizi (Jurnal Pendidikan Matematika, 2025)
This article is devoted to the role, content, and opportunities for effective teaching of elements of Probability Theory and Mathematical Statistics in the mathematics curriculum of general secondary education. It reveals the necessity of explaining the fundamental concepts of school-level probability theory—such as event, event probability, and its definitions, as well as probability calculation—through practical problems, and provides relevant problem examples. In the international PISA assessment test, questions related to this subject are also included, and students from our country have shown low performance specifically in these types of questions. This indicates that a special approach is needed for teaching this subject. In other words, in teaching the subject, it is necessary to increase students' interest through practical problems, strengthen their knowledge, and ensure that the lesson process is conducted effectively. In conclusion, it can be stated that the use of real-life, interdisciplinary, and integrated problems by the teacher in the lesson process serves to increase the effectiveness of the lesson, engage more students in the learning process, and develop their logical, statistical, and probabilistic thinking